THE INFLUENCE OF GREEN MARKETING MIX ON BUYING INTEREST FOR BODY SHOP PRODUCTS IN ACEH - Puja Ramadhani; Sapna Biby; Mariyudi; Rahmaniar (RADJA PUBLIKA, 2024)
The purpose of this study was to analyze and determine the effect of green product, green place, green price and green promotion on buying interest in The Body Shop products. This type of research is quantitative research with a population of consumers in Lhokseumawe City. The number of respondents was 140 people who were taken using purposive sampling technique. The data source comes from primary data obtained through distributing questionnaires. The data analysis technique used is descriptive analysis method and multiple linear regression analysis, classical assumption test, instrument test (validity and reliability), hypothesis testing and determination coefficient test and correlation test and analyzed with the help of SPSS application program. The results of this study indicate that simultaneously green product, green price, green place and green promotion have a positive and significant effect on buying interest in The Body Shop products. While partially the variables green product, green price, green place and green promotion have a significant influence on buying interest. Green promotion is the most dominant variable affecting buying interest with a t value of 3.485.